P080 Investigating the effects of accelerated partner therapy on chlamydia transmission in britain: a mathematical modelling study. (14th July 2019) - Althaus, Christian; Mercer, Catherine; Cassell, Jackie; Estcourt, Claudia; Low, Nicola
Abstract : Background: Understanding the effects of partner notification (PN) on chlamydia transmission is critical for implementing optimal control strategies. Accelerated partner therapy (APT) aims to reduce the time to partner treatment and increase the proportion of partners treated. As part of LUSTRUM, a PN trial in the UK, our objective was to study the effects of APT interventions on partner treatment and chlamydia transmission using a mathematical model. Methods: We developed a deterministic, population-based chlamydia transmission model including the process of PN. We considered a heterosexual population aged 16–34 years and calibrated the model to sexual behaviour and chlamydia prevalence data reported by 3, 671 participants in Britain's third National Survey of Sexual Attitudes and Lifestyles (Natsal-3, 2010–2012) using Approximate Bayesian Computation (ABC). We investigated the potential effects of APT on chlamydia transmission by reducing the time to partner treatment and increasing the proportion of treated partners compared to standard PN. Results: The median prevalence of chlamydia in the model was 1.8% (95% credible interval (CrI): 1.6%-2.6%) in women and 1.7% (95% CrI: 1.1%-2.1%) in men. Overall, chlamydia-positivity in partners of index cases was 55% (95% CrI: 31%-79%), and higher in partners of symptomatic index cases (76%) than asymptomatic index cases (33%). Reducing the time to partner treatment without achieving higher proportions of partners treated had only small effects on reducing chlamydia prevalence. In contrast, the model predicts that a potential increase in the proportion of partners treated from current levels in the UK (36%, 95% CrI: 13%-96%) by 25% would reduce chlamydia prevalence by 14% (95% CrI: 3%-40%) in women and by 14% (95% CrI: 3%-39%) in men within 5 years. Conclusion: Our results suggest that APT, through an increase in the proportion of partners treated, would be an effective method to reduce ongoing chlamydia transmission in the UK. Disclosure: No significant relationships.